Indole Hydrazide Derivatives as Potential Corrosion Inhibitors for Mild Steel in HCl Acid Medium: Experimental Study and Theoretical Calculations - Sunil, Dhanya; Kumari, Preethi; Shetty, Prakash; Rao, Suma A (Transactions of the Indian Institute of Metals, 2022)
The present work highlights the corrosion inhibition action of two indole-3-hydrazides with varying alkyl chain lengths: 2-(1 H -indol-3-yl)acetohydrazide (IAH) and 4-(1 H -indol-3-yl)butanehydrazide (IBH) against mild steel (MS) in 0.5 M hydrochloric acid (HCl) solution using electrochemical and gravimetric measurement methods. Both IAH and IBH behaved as mixed-type inhibitors, and their anticorrosion behaviour was due to a protective film formation on MS surface through physisorption, in agreement with Langmuir’s adsorption model. The surface morphologies of the inhibited specimens examined using SEM and AFM images showed distinctive improvement against acid corrosion. The quantum mechanical calculations indicated the contribution of delocalized π-electrons in the indole unit and the lone-pair electrons in the carbonyl group for improved adsorption of the studied hydrazides onto the metal surface, supporting the experimental results. IAH and IBH showed maximum inhibition efficiency of 80.4 and 94.1% at 30 °C in MS exposed to 0.5 M HCl medium at its optimum concentration. The better resistance to MS corrosion was exhibited by the acid system-containing IBH bearing three methylene groups and hence having higher molar volume and surface coverage in comparison with IAH that incorporated only one methylene group in its chemical structure.